Plot size and number of replicates for experiments with forage sorghum - Toebe, Marcos; Cargnelutti Filho, Alberto; Souza, Rafael Rodrigues de; Soares, Franciele dos Santos; Mello, Anderson Chuquel; Melo, Patrícia Jesus de; Silva, Lucas Santos da (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to define the optimal plot size and number of replicates for the evaluation of the fresh weight of sorghum (Sorghum bicolor) hybrids. Thirty-two uniformity trials were carried out with two hybrids, in two sowing dates and four evaluation periods. Each trial was divided into 48 basic experimental units (BEUs) of 0.5 m2, and fresh weight was determined for each BEU. The mean, variance, coefficient of variation , first-order spatial autocorrelation coefficient, optimal plot size, and coefficient of variation of the optimal plot size were calculated. The number of replicates was determined on the basis of the largest calculated plot size, through an iterative process, for the combinations of number of treatments and differences among means to be detected as significant by Tukey’s test, at 5% probability. The optimal plot size ranged from 1.79 to 2.58 m2, and the number of replicates from 2.6 (~3) to 49.2 (~50). The optimal plot size is 2.58 m2, and five replicates are sufficient to identify as significant the differences between treatment means of 35%.
Keywords: Sorghum bicolor; experiment planning; uniformity trials